Hubungan Budaya Tim, Berbagi Pengetahuan dan Komitmen Karyawan Dalam Meningkatkan Kinerja Karyawan - Dewi Siti Patimah; Andi Hidayat Muhmin (Economic Reviews Journal, 2025)
Employee skills and knowledge are essential in achieving optimal performance to realize a company's vision and mission. Therefore, fostering strong teamwork and synergy among employees is crucial. A collaborative team culture not only facilitates knowledge sharing and enhances employee commitment but also leads to higher performance. This study aims to examine the relationship between team culture and knowledge sharing, employee commitment, and their impact on employee performance. The research population consists of employees at PT Kawasan Berikat Nusantara (KBN), with purposive sampling applied to select respondents based on specific criteria: employees from various divisions with a maximum of two years of work experience in the Jakarta region, totaling 190 respondents. Structural Equation Modeling (SEM) using Partial Least Squares (PLS) was employed to analyze the relationships between variables. The findings confirm that team culture has a direct positive effect on employee commitment, knowledge sharing, and performance. Additionally, both employee commitment and team culture directly influence employee performance at PT Kawasan Berikat Nusantara (KBN). The study concludes that all hypothesized relationships are supported, demonstrating that a well-implemented team culture significantly enhances knowledge sharing, commitment, and employee performance. Academic and practical contributions this research contributes to human resource management theory by reinforcing the role of team culture in organizational performance. For practitioners, the findings provide a foundation for designing training programs and policies that strengthen team collaboration and knowledge exchange among employees